Comparison of methods for phenotypic adaptability and stability analysis in common bean - Pereira, Helton Santos; Melo, Leonardo Cunha; Peloso, Maria José Del; Faria, Luís Cláudio de; Costa, Joaquim Geraldo Cáprio da; Díaz, José Luíz Cabrera; Rava, Carlos Augustín; Wendland, Adriane (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to compare methods for studying phenotypic adaptability and stability in common beans (Phaseolus vulgaris). Grain yield evaluations were carried out in 71 trials with 16 common bean genotypes, and using six methods. The association among the methods was determined by Spearman correlation. Cruz and Eberhart & Russel methods were highly correlated. Lin & Binns, Lin & Binns modified and Annicchiarico methods were also highly correlated. Intermediate correlations were observed between Eberhart & Russel and additive main effects and multiplicative interaction model (AMMI) methods. The joint utilization of highly correlated methods is not recommended. Therefore, only one of the methods among Eberhart & Russel, Cruz and AMMI should be used in association with Lin & Binns, Lin & Binns modified or Annicchiarico, since there was no correlation among methods of these two groups. Lin & Binns and Annicchiarico methods are indicated for isolated utilization, because they are simple to use and allow the classification of environments in favorable and unfavorable, and the identification of the most adapted and stable genotypes among the most productive ones.